Assesment Manajemen Risiko Berdasarkan ISO 31000 pada UMKM Industri Kreatif Rajut: Studi Kasus Diva Salsabilla Niaga Kota Bandung - Chika Putri Irwanda; Nira Destiani Dewi; Nabila Zulfa Azizah; Nurul Laily Oktaviana; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze the implementation of risk management at Diva Salsabilla Niaga, a home-based industry engaged in the production and sale of knitted products. The business has been operating for five years and employs around 89 people, consisting of administrative staff, marketing personnel, production teams, and expedition workers. The products are sold offline and have recently begun to be marketed online through the TikTok platform. This research focuses on identifying the main risks faced by the business and the strategies implemented to maintain stable and efficient operations. The research employs a qualitative descriptive approach, with data collected through direct interviews with the business owner. The findings show that the main risks faced include production failure, limited capital, lack of human resources, rising raw material prices, and changes in fashion trends and economic conditions. To address these challenges, the owner implements preventive measures such as producing based on orders, maintaining product quality control, preparing raw material stocks before peak seasons, and fostering effective communication and teamwork. Proper implementation of risk management enables Diva Salsabilla Niaga to maintain business continuity and serves as a crucial foundation for enhancing competitiveness in the creative knitting industry sector..